Kejadian Infeksi Luka Operasi pada Pasien Post Operasi Apendiktomi - Atira Atira; Emy Salmiyah; Dede Puri Purwandi (GLOBAL HEALTH SCIENCE, 2021)
The incidence of appendicitis at the Cimacan Hospital, West Java within a period of six months in 2019 was 43 cases. The incidence of appendicitis generally experiences surgical wound infections (ILO) in every month, but the number of ILO incidences is not known. The purpose of this study was to determine the profile of ILO cases in post-operative appendectomy patients at the Surgical Clinic at Cimacan Hospital in 2020. The research method used was the Descriptive Survey Method with data collection using a Guttman scale questionnaire sheet in appendicectomy patients. The sample used was 30 respondents with a sampling technique using purposive sampling. The results showed that based on the Univariate Analysis Test, the results obtained were from as many as 30 respondents there were 17 (56.7%) who had surgical wound infections (ILO) in appendectomy patients and 13 (43.3%) respondents did not experience ILO. Suggestion: it is necessary to promote health regarding the importance of knowledge about wound care in appendectomy patients to the medical team and family so that the prevention of surgical wound infection (ILO) can be avoided. Keywords: surgical wound infection; appendectomy patient ABSTRAK Angka kejadian apendisitis di RSUD Cimacan, Jawa Barat dalam kurung waktu enam bulan pada tahun 2019 terdapat 43 kasus. Kejadian apendisitas umumnya mengalami infeksi luka operasi (ILO) dalam tiap bulan, namun belum diketahui jumlah angka kejadian ILO. Tujuan penelitian ini adalah untuk mengetahui profil kasus ILO pada pasien Post Operasi Apendiktomi di Poli Bedah RSUD Cimacan tahun 2020. Metode penelitian yang digunakan yaitu Metode Survei Deskriptif dengan pengambilan data menggunakan lembar kuesioner skala guttman pada pasien Apendiktomi. Sampel yang digunakan sebesar 30 responden dengan teknik pengambilan sampel menggunakan purposive sampling. Hasil penelitian menunjukkan bahwa berdasarkan Uji Analisis Univariat didapatkan hasil yaitu dari sebanyak 30 responden terdapat 17 (56,7%) yang mengalami infeksi luka operasi (ILO) pada pasien apendiktomi dan lainnya sebesar 13 (43,3%) responden tidak mengalami ILO. Saran: perlu dilakukan promosi kesehatan mengenai pentingnya ilmu pengetahuan tentang perawatan luka pada pasien apendiktomi pada tim medis dan keluarga agar pencegahan infeksi luka operasi (ILO) dapat terhindarkan. Kata kunci: infeksi luka operasi; pasien apendiktomi